2007
DOI: 10.1016/j.colsurfa.2006.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-functionalized silica colloids, grains, and membranes for irreversible adsorption of metal(oxide) nanoparticles

Abstract: Thiol-functionalization is described for silica surfaces from diverging origin, including commercial silica nanoparticles and Stöber silica as well as silica structures provided by porous glasses and novel polymer-templated silica membranes. The functionalization allows in all cases for the irreversible binding of metal(oxide) particles from a solution. Examples are the adsorption of CoFe 2 O 4 particles for the preparation of magnetizable silica colloids and silica structures, and gold nanoparticles that dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…A layer of dodecane thiol was first formed on the substrate to enhance particle attachment. Claesson and Philipse [32] have reported that the surface functionalization of silica using thiol allows the irreversible binding of metal oxide particles from a solution. A similar procedure was followed for the surface functionalization of the polyethylene substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A layer of dodecane thiol was first formed on the substrate to enhance particle attachment. Claesson and Philipse [32] have reported that the surface functionalization of silica using thiol allows the irreversible binding of metal oxide particles from a solution. A similar procedure was followed for the surface functionalization of the polyethylene substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate was treated with 1% dodecane thiol solution in ethanol and then heated at 100 • C for 15 min prior to the ZnO nanowire growth [32]. The substrates were seeded by dipping the thiolated substrates into a concentrated colloidal solution of ZnO nanoparticles in isopropanol for 15 min.…”
Section: Hydrothermal Growth Of Zno Nanowiresmentioning
confidence: 99%
“…This dialysis was needed for a surface functionalization, which cannot be done in water. 22 Since this dialysis transfer to ethanol does not affect the colloidal stability of the silica particles, 22 we can compare the results from DLS and SV AUC measurements on aqueous silica sols.…”
Section: Methodsmentioning
confidence: 99%
“…As both ϕ-MSGNRs and β-MSGNRs possess regions of uncoated gold and one/two silicaencased end(s), two types of surfaces are available on these moieties for modification/functionalization; especially noteworthy in that both silica and gold can be readily modified for ligand conjugation via biocompatible silane and thiol functional groups, respectively. 31,32 Since the tips of GNRs are known to exhibit significant surface Raman enhancement and metal-enhanced fluorescence, ϕ-MSGNRs and β-MSGNRs also afford the opportunity to selectively modify Raman or fluorescent probes at the most efficacious sites.…”
Section: -25mentioning
confidence: 99%